Critical Care Communication Skills Training for Internal Medicine Residents - Laura Rock; Nina Gadmer; Robert Arnold; David Roberts; Asha Anandaiah; Melanie Pogach; Peter Clardy; Richard Schwartzstein; Amy Sullivan (Association of American Medical Colleges, 2015)
Abstract Good communication is at the heart of excellent care for patients and families. At the Beth Israel Deaconess Medical Center Shapiro Institute for Education and Research, we have developed a communication training program for our internal medicine residents. During their intensive care unit (ICU) rotation, residents participate in weekly sessions to learn about key elements for compassionate, effective communication with family members of critically ill patients. The course focuses on teaching skills needed in initial meetings with families of critically ill patients such as answering family members' urgent questions, helping them understand and cope with the patient's illness, and responding to family members' distress, anger, or sadness. Residents are also taught how to sensitively lead family meetings later in the course of care, especially in discussing important decisions about goals of care when cure is unlikely and the patient's comfort and quality of life are paramount. Given the 3-week ICU rotation, the course is designed to be delivered in three parts over 4 hours: 1-hour sessions for the first 2 weeks and a 2-hour simulation session in the third week. Response rate for residents is 98% (n = 137). Residents are 54% male, 69% white, 20% Asian, 4% African American, and 7% other. Prior to training, 97% of residents felt that communication with family members was "very important"; however, few had any other communication training during residency, and many felt underprepared for carrying out important communication tasks. After the course, residents reported statistically significant improvements (p < .0001) in preparation to carry out all 17 surveyed skills, with moderate to high effect sizes (e.g., preparation to lead family meetings, 1-5 scale, 2.5-3.5; understanding of appropriate language to use in family communication, 2.5-3.4, p < .0001). Resident attitudes changed as well: Residents were more likely to agree that they wished they could lead more family meetings (pre vs. post: 15.4% vs. 69.3%), more comfortable talking to family about the possibility of death (30.1% vs. 84.6%), and less likely to agree that they dreaded having to deal with the emotional distress of family members of a patient at the end of life (53.8% vs. 23.1%).